Semi-Empirical Model of Tire-Pavement Contact - P. Fundowicz; J. Wicher (Engineering Transactions, 2015)
Mathematical model of the tire-pavement interaction is presented in the paper. One of the main features of the model is easy identification of the parameter values by means typical testing equipment. In the model the contact zone of the tire is divided into the adhesion zone and the slip zone. Influence of the water wedge has been examined. Some typical tire characteristics are shown as a result of application of the proposed model.